A new species of Pothea, with new records and taxonomic notes on other species of the genus (Hemiptera: Heteroptera: Reduviidae) - Gil-Santana, Hélcio R. (Zootaxa, 2020)
Pothea carpinteroi sp. nov. (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae) is described based on two male specimens from Mexico. Pothea aeneonitens Stål, 1864 and P. lugens (Fabricius, 1803) are recorded from French Guiana for the first time. Taxonomical notes on these latter two species and P. haematogaster Breddin, 1903 and P. sanguiniventris Miller, 1956 are also presented. A lectotype is designated for P. lugens. Pothea centralis Walker, 1873, treated as a junior synonym of P. lugens by previous authors, is regarded as a potentially valid species. Color variation in the sternites of males and females of P. frontalis (Lepeletier & Serville, 1825) are recorded for the first time. Photographs of the type specimens of P. aeneonitens, P. bivittata Champion, 1899, P. centralis, P. frontalis, P. haematogaster, P. halffteri Carpintero, 1980, P. lugens, P. maculata Champion, 1899, P. reyesi Carpintero, 1980, P. sanguiniventris and P. venatrix Hussey, 1953, are presented.